Distance Learning Environment and Intrinsic Motivation of Students of Social Science Education, State University of Jakarta - Rizky Nurisriyani; Dian Alfia Purwandari; Sujarwo Sujarwo (Universitas Muhammadiyah Enrekang, 2021)
Distance Learning in the Covid-19 pandemic era has become an alternative used by every university so that the learning process activities continue even though it is only face-to-face so that educational goals are achieved effectively and efficiently. This study aims to analyze the effect of the Distance Learning Environment on Intrinsic Motivation in learning for students of the Social Sciences Education study program. The method used in this research is quantitative research method with the sampling technique used is cluster sampling. The population used in this study were 252 social studies education students batch 2018-2020, while the sample used was 155 respondents. Based on the results of the t-test, the results obtained are t-count 8.384 > t-table 1.975, which means that there is an influence of the Distance Learning Environment variable on Intrinsic Motivation in learning in students of the Social Sciences Education study program. This is reinforced by the acquisition of the coefficient of determination test results of 31.3%.